Application of case-based transferable belief model to pattern classification - Arıbaş, Kaya Mustafa (My University, 2020)
Bu tezde, savaş gemilerini tiplerine göre otomatik olarak sınıflandıran Aktarılabilir İnanç Modeli tabanlı bir sınıflandırıcı gerçeklenmiştir. Sınıflandırıcı, Duruma Özgü Sınıflandırıcı olarak adlandırılmıştır. Sınıflandırıcıya veri sağlayan algılayıcıların elde edilen ölçümlerde belirsizlik olduğu varsayılmıştır. Aktarılabilir İnanç Modeli bu belirsizliği modellemede Bayesian Teorisi ve Bulanık Küme Teorisi gibi diğer geleneksel yöntemlerden daha başarılıdır. Ayrıca, Aktarılabilir İnanç Modeli farklı algılayıcılardan gelen bilginin birleştirilmesine olanak sağlamakta ve bu bilgiler arasında var olabilecek bir çelişkiyi de saptayabilmektedir. Bu çalışma için oluşturulan yapay bir veri tabanı üzerinde Duruma Özgü Sınıflandırıcının sınıflandırma başarımı tespit edilmiştir ve gerçek problemlere uygulanabilir olduğu gösterilmiştir.

In this thesis, a classifier based on the Transferable Belief Model is implemented to classify warships automatically according to their type. The classifier is called as the Case Based Classifier. Uncertainty was assumed to exist in the measurements obtained from the sensors that provide data to the classifier. The Transferable Belief Model is more successful in modelling this uncertainty than the conventional methods such as Bayesian Theory and Fuzzy Set Theory. In addition, the Transferable Belief Model allows the fusion of information coming from different sensors it can detect any conflict that may exist among the measurements obtained from different sensors. Classification performance of the case-based classifier was identified on an artificial database and it was shown to be applicable to real-world problems.
Keywords: aktarılabilir inanç fonksiyonu; belief function theory; classification; conflict detection; çelişki tespiti pattern recognition; Electric engineering; Electronics engineering; Elektrik mühendisliği; Elektronik mühendisliği; inanç fonksiyonu teorisi; örüntü tanıma; sınıflandırma; transferable belief model